Detailed Methodology and Implementation of a Semiautomated Serial Dilution Microtechnique for Antimicrobial Susceptibility Testing - MacLowry, James D. (1970)
The detailed methodology and implementation of a semiautomatic microtechnique for performing serial dilution antimicrobial susceptibility studies are described. Quantitative susceptibility studies to a battery of antimicrobials are performed routinely on all significant clinical isolates. Results are reported as the minimal inhibitory concentration in micrograms per milliliter of broth. Guidelines relating standard doses of antimicrobials with expected blood and urine levels are presented to facilitate the use of the quantitative data. This microtechnique is used to measure serum and other body fluid levels of antimicrobial agents to document the level attained with a specific course of therapy. This technique is highly reproducible and has a high correlation with, and is at least 10 times faster than, standard glass tube techniques.